2012
DOI: 10.1002/uog.10154
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence after primary repair of obstetric anal sphincter tears is related to relative length of reconstructed external sphincter: a case–control study

Abstract: Objective To determine if anatomic primary repair with end-to-end reconstruction of the external anal sphincter (EAS) in its full

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…Previous studies suggest that a shorter anal sphincter length following primary repair of OASI is associated with poorer outcomes. 31 In contrast, we found no association between anal sphincter length as measured by way of manometry and post-intervention AI symptoms.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies suggest that a shorter anal sphincter length following primary repair of OASI is associated with poorer outcomes. 31 In contrast, we found no association between anal sphincter length as measured by way of manometry and post-intervention AI symptoms.…”
Section: Discussioncontrasting
confidence: 77%
“…In addition to the higher Wexner score, the patients in the failed primary repair group had a significantly higher proportion of EAS defects on EAUS. The correlation of Wexner scores with EAUS findings has been shown in past research . This suggests that the Wexner scoring system could be a cost‐effective and potent tool in screening patients who require additional imaging studies of the anal sphincter complex because of a possible occult OASI.…”
Section: Discussionmentioning
confidence: 58%
“…As these tears typically affect the anterior parts of the sphincters, it was necessary to avoid this possible bias by only assessing women in whom preexisting sphincter defects were highly unlikely. Future studies may explore the extent of the anterior gap and the length of the anterior EAS in both continent and incontinent parous women, as the relative length of the anterior EAS seems to be inversely associated with incontinence at least in women who have sustained obstetric sphincter tears 7 . Finally, the study was undertaken in white women only, and the findings will not necessarily apply to other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, defects diagnosed by EAUS correlate with findings at reconstructive sphincter surgery 5 . Two different scoring systems have been developed to classify the 3D extent of sphincter defects, 3,6 and studies have shown that larger defects with higher scores are associated with more severe incontinence than smaller defects with lower scores 7–9 . Both scoring systems include partial EAS defects, defined as ultrasound (US) defects involving greater than 50% but less than 100% of the EAS thickness.…”
mentioning
confidence: 99%
See 1 more Smart Citation